Security System in A Private Room Using Esp32 Microcontroller with Telegram Bot - Antono, Dhovem Ramadhani Riandy; Suryo, Yoedo Ageng (Journal of Energy and Electrical Engineering, 2025)
Losing valuables in private rooms remains a common issue, often caused by the limitations of conventional security systems. This research proposes the design and implementation of a modern security system based on the ESP32 microcontroller integrated with a Telegram bot to provide real-time monitoring and control. The system is engineered to detect suspicious movements within a room and immediately notify the owner via the Telegram application. It consists of key components including a power supply unit, motion sensors for activity detection, the ESP32 microcontroller as the central processing unit, and the Telegram bot as the communication interface. When motion is detected, sensor data is transmitted to the ESP32, which processes the input and sends automated alerts through Telegram. Additionally, the system features remote control capabilities, allowing users to lock or unlock the room via Telegram commands. Testing results indicate that the system demonstrates high motion detection accuracy and fast response times with minimal latency in message delivery. The implementation of this tool significantly enhances room security and provides a practical solution for preventing the loss of valuables in personal spaces.